PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA POKOKBAHASAN TRIGONOMETRI KELAS XSMA BERSTANDAR NCTM(NATIONAL COUNCIL OF TEACHERS OF MATHEMATICS) - N, Indah Syurya; Hobri, H; Kristiani, Arika Indah (KadikmA, 2013)
Abstract.This research aims to know how the process and the result of developing mathematics learning materials based on NCTM (National Council of Teachers of Mathematics) of trigonometry topic at grade X senior high school. This study developessyllabus, lesson plan,worksheet, evaluation test, and Studentbook.The development mathematics learning materials standardized NCTM. This development model refers to 4-D Thiagarajan and Sammel & Samel models. This four steps are defining step, designing step, developing step, and disseminating step.The product of learning materials development standardized by NCTMfortrigonometry topic has fulfilled the validation criteria, practicability, and effectiveness. Key Words:Learning Materials, NCTM, Trigonometry.